Comparison of superficial site infection between delayed primary and primary wound closures in ruptured appendicitis - Meka, Mohanakrishna; Anasuri, Bhaskar (International Surgery Journal, 2018)
Background: The aim of the study was to compare the superficial surgical site infections between delayed primary closures and primary closures in ruptured appendicitis. Methods: This study was a retrospective study conducted in Chalmeda Anand Rao Institute of Medical Sciences, Karimnagar during the period of August 2012 to October 2015. Results: 86 patients with ruptured appendicitis were eligible and their data were retrieved; 66 (76.7%) patients had received DPC and 20 (23.3%) patients had received PC. The SSI rate was much lower in PC patients than in DPC patients. There was an approximately 77% lower risk of SSI in the PC group than in the DPC group, but this did not reach statistical significance. Conclusions: This study concluded that in ruptured appendicitis, risk due to SSI showed no difference between PC and DPC techniques. In low risk SSI patients, PC does not increase risk of SSI